#### Answer

$3$

#### Work Step by Step

$\lim\limits_{x \to 0} { \frac{x-3}{x-1} } = \lim\limits_{x \to 0} { \frac{0-3}{0-1} } = \lim\limits_{x \to 0} { \frac{-3}{-1} } = 3$

Published by
Brooks Cole

ISBN 10:
1133607705

ISBN 13:
978-1-13360-770-0

$3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.